2022
DOI: 10.3390/microorganisms10081630
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Presentation of Aspergillus niger Infection in the Oral Cavity as a Prediction of Invasive Pulmonary Aspergillosis in a Patient with COVID-19: Case Report and Literature Review

Abstract: Coinfections between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and other respiratory pathogens such as Aspergillus have become challenging, as well as being associated with high morbidity and mortality in patients with COVID-19. Aspergillus niger is a common environmental mold. Before the emergence of COVID-19, it was considered a very rare cause of invasive pulmonary aspergillosis (IPA), occurring mainly in immunocompromised patients. The aim of this study was to describe a very rare case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Aspergillus niger is among the most common fungi, responsible for post-harvest decay of fresh fruit, fish products and meat products [ 34 , 35 ]. Only the A. yentunensis EO with high amounts of safrole (64.74%) and sesquicineol (15.34%) was likely responsible for these antifungal activities.…”
Section: Resultsmentioning
confidence: 99%
“…Aspergillus niger is among the most common fungi, responsible for post-harvest decay of fresh fruit, fish products and meat products [ 34 , 35 ]. Only the A. yentunensis EO with high amounts of safrole (64.74%) and sesquicineol (15.34%) was likely responsible for these antifungal activities.…”
Section: Resultsmentioning
confidence: 99%
“…One study indicated that GCF can even serve as a potential medium for evaluating the mycobiome, as it revealed the presence of Aspergillus niger in a patient with COVID-19 and could predict the occurrence of an invasive aspergillosis infection. These tests may be even faster and more sensitive than traditional serum examinations (including antigen tests) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such critically ill COVID-19 patients, when admitted to the intensive care unit (ICU) and requiring mechanical ventilation, are more likely to develop healthcare-associated infections [ 12 , 13 ]. Cases of both bacterial and fungal infections were reported, with studies focusing on multidrug resistant bacterial strains, mucormycosis, and aspergillosis [ 12 , 14 , 15 , 16 ]. As Candida spp.…”
Section: Introductionmentioning
confidence: 99%